2019
DOI: 10.1080/15226514.2019.1612847
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic-enhanced phytoremediation of uranium-contaminated soil using sunflower and Indian mustard

Abstract: Electrokinetic-enhanced phytoremediation is an effective technology to decontaminate heavy metal contaminated soil. In this study, we examined the effects of electrokinetic treatments on plant uptake and bioaccumulation of U from soils with various U sources. Redistribution of uranium in soils as affected by planting and electrokinetic treatments was investigated. The soil was spiked with 100mg kg -1 UO2, UO3, and UO2(NO3)2. After sunflower and Indian mustard grew for 60 days, 1 voltage of directcurrent was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
5
9
0
Order By: Relevance
“…Lowering the soil pH often increases the bioavailability of most metals in soil. Our results were consistent with our previous pot study …”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Lowering the soil pH often increases the bioavailability of most metals in soil. Our results were consistent with our previous pot study …”
Section: Resultssupporting
confidence: 94%
“…The shoot U concentrations in the anode region were higher than those in the cathode region, which was ascribed to soil acidification (pH = 2.7) and the activation of soil U in the anode region. These results were consistent with our previous pot study and were similar to the results by O’Connor et al The results also indicated that more U was accumulated in shoots than that in roots with the initial EKF. The grass showed different tolerances to various U species in soils.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Bioaugmentation with Paracoccus MAL 1HM19 enhanced the oxidation of the accumulated S 0 to sulfate in the anoxic BTF. Li, Zhang, Larson, et al (2019) coupled an EK process with phytoremediation to remove uranium from soils containing different uranium compounds, UO 2 , UO 3 , and UO 2 (NO 3 ) 2 . EK process could enhance the removal efficiency at different levels (e.g., UO 3 was the most and UO 2 was not significantly removed).…”
Section: Biofiltersmentioning
confidence: 99%